The molecular mechanism of Gaucher disease caused by compound heterozygous mutations in GBA1 gene - Liu, Qi; Shen, Zongrui; Pan, Hong; Ma, Shunfei; Xiong, Fu; He, Fei (Frontiers in Pediatrics, 2023)
Gaucher disease (GD, ORPHA355) is a rare autosomal recessive genetic disease caused by mutations in GBA1, which encodes the lysosomal enzyme glucocerebrosidase (GCase). Here, we report a patient with GD who carried the heterozygous c.1240G > C (p.Val414Leu) mutation and the heterozygous pathogenic c.1342G > C (p.Asp448His) mutation in GBA1. Bioinformatics analysis suggested that the two mutations are pathogenic. Functional studies showed that GBA1 mRNA and GCase protein levels of mutant types were significantly less than the wild-type. In the cell lysates, the two mutations of GBA1 c.1240G > C and c.1342G > C caused a decreased GCase concentration, while the two mutations did not change the distribution in the cell. The pathogenicity of the compound heterozygous mutations was verified. Early diagnosis and treatment can improve the quality of life and prevent unnecessary procedures in patients with GD.